2022
DOI: 10.7860/jcdr/2022/59239.17093
|View full text |Cite
|
Sign up to set email alerts
|

Kangaroo Mother Care versus Prone Position in Preterm Neonates: A Non Randomised Clinical Study

Abstract: Introduction: One of the major problems of preterm neonates is immature alimentation. This may lead to inadequate weight gain, higher chances of sepsis and increased mortality. Positioning during and after feeding affects nutritional tolerance. Kangaroo Mother Care (KMC) is a method of skin-to-skin contact between mother and neonate, claimed to improve infant outcomes. Aim: To compare prone and Kangaroo Mother Care positioning of preterm neonates of 28 to 32 weeks gestational age during orogastric tube feedin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…The primary results of the studies included in the systematic review are presented in Table 5. In the studies by Özdel and Sarı 18 , no significant difference was found between the prone position and kangaroo care in terms of mean gastric residual volumes, whereas the study by Naskar et al 25 found less stomach residual volume in kangaroo care compared with the prone position. In the study of Yayan et al, the stomach residual volume level was lower in the right lateral and prone positions than in the left lateral and prone positions 15 .…”
Section: Resultsmentioning
confidence: 90%
See 4 more Smart Citations
“…The primary results of the studies included in the systematic review are presented in Table 5. In the studies by Özdel and Sarı 18 , no significant difference was found between the prone position and kangaroo care in terms of mean gastric residual volumes, whereas the study by Naskar et al 25 found less stomach residual volume in kangaroo care compared with the prone position. In the study of Yayan et al, the stomach residual volume level was lower in the right lateral and prone positions than in the left lateral and prone positions 15 .…”
Section: Resultsmentioning
confidence: 90%
“…Also, considering that most studies 16,19–22,24 recommended the prone position for its effectiveness on stomach residual volume, it seems kangaroo care has an effect similar to the prone position with the infant's contact with the mother. However, in the studies of Naskar et al, the amount of stomach residual volume in kangaroo care was less than in the prone position with regards to mean gastric residual volumes measured 3 h after feeding 25 . This could be because the participants in the study by Naskar et al 25 were preterm newborns at 28–32 weeks of gestation compared with the sample group of Özdel and Sarı, 18 which included newborn infants at 28–36 weeks of gestation, possibly leading to different results.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations